PENGEMBANGAN ENSIKLOPEDIA DIGITAL "WHAT'S WRONG WITH MY BODY?" UNTUK MENINGKATKAN PERSONAL HYGIENE SISWI KELAS VI SEKOLAH DASAR - Rahmania Mutiarasari, - (2023)
This study aims to describe the initial design, initial product, expert validation results, and final product of the digital encyclopedia entitled "What's Wrong with My Body?" to improve personal hygiene of grade VI elementary school students. This research was motivated by the lack of understanding of grade VI students about personal hygiene in facing puberty caused by the lack of media to learn about personal hygiene, especially for girls who have gone through puberty. This can be overcome by developing special learning media for women about puberty, reproductive organs, and personal hygiene that is carried out every day, week, and month, as well as developing a personal hygiene journal for readers to fill. This research is a Design and Development (D&D) development research using the PPE model. Data collection techniques are carried out through the distribution of validation questionnaire instruments to media, material, and learning experts as well as readability tests to grade VI elementary school students. The stages carried out in this research begin with making an initial design of the results of problem analysis, basic competency analysis, and material analysis. After getting the initial product, the product is validated by experts and readability tested. The validation results become the basis for the revision of the final product by changing two illustrations in the content of the material. Based on the research that has been done, it can be concluded that the encyclopedia developed by researchers is suitable for use and can help to improve personal hygiene of grade VI elementary school students.